Transmission Expansion and Electricity Trade: A Case Study of the Greek Power System - Koltsaklis, Nikolaos E.; Dagoumas, Athanasios S. (International Journal of Energy Economics and Policy, 2018)
The integration of European electricity markets, through the market coupling process, can create significant efficiency gains in terms of social welfare to European consumers and industries. The market coupling process is anticipated to more efficiently utilize the generation and transmission activities, reducing the requirements of large idle generation capacity. This paper uses an optimization-based methodological framework to address the problem of the optimal planning of a power system at an annual level in competitive and volatile power markets, under dynamic formulation of the strategy employed by all market participants. The model is used for the scenario-based transmission expansion of the Greek power system with neighboring power systems in Southeast Europe, identifying its impact on a series of operational and economic aspects. The model determines the optimal power generation mix in each scenario, the electricity trade with the neighboring countries, the evolution of the system marginal price and the resulting environmental impact. This enables the identification of the remuneration of all types of producers from the wholesale market through a detailed calculation of all the relevant cost components. The proposed approach can provide useful insights on the optimal portfolio determination by potential investors at a national and/or regional level, highlighting potential risks and appropriate price signals on critical infrastructure projects under real electricity market operating conditions. Keywords: CO2 emissions; Electricity trade; Power market dynamics; Power generation mix; Transmission expansion JEL Classifications: Q43, Q47